1991
DOI: 10.1002/anie.199101021
|View full text |Cite
|
Sign up to set email alerts
|

The Reduction of the NbX5/AlX3 System with Aluminum in the Presence of Aromatic Hydrocarbons: An Approach to Niobium(II), Niobium(I), and Niobium(0) Organometallics

Abstract: The additional occupation of the face centers of the M, octahedron of a M,X,, cluster is observed for the first time in Th,Br,,H,; this type of occupation is already known for systems with condensed clusters. In the compounds ZrXH (X = C1, B I -) [ '~~ and LnXH,[I5] two H atoms assume positions in opposite faces of elongated trigonal antiprisms of M atoms (d(D-D) = 220 pm in the case of ZrBrD and 298 pm in the case of TbBrD,).The number of bonding orbitals in the Th,Br,,H, cluster is the same as in the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…The most common routes for generating low-valent early transition metal complexes involve the reduction of metal halides with strong alkali metals 2732 ; reduction with other (often weaker) reducing metals, such as Mg (REFS 33,34 ), Mn (REF. 35 ), Al (REFS 36,37 ) or Zn (REF. 38 ) (providing more functional group tolerance); or p-H abstraction 3943 from a metal alkyl (Fig.…”
Section: Generation Of Low-valent Complexesmentioning
confidence: 99%
“…The most common routes for generating low-valent early transition metal complexes involve the reduction of metal halides with strong alkali metals 2732 ; reduction with other (often weaker) reducing metals, such as Mg (REFS 33,34 ), Mn (REF. 35 ), Al (REFS 36,37 ) or Zn (REF. 38 ) (providing more functional group tolerance); or p-H abstraction 3943 from a metal alkyl (Fig.…”
Section: Generation Of Low-valent Complexesmentioning
confidence: 99%
“…It was later found that a 30-50% yield of (r|-C 6 H 3 Me 3 ) 2 Nb can be isolated from the reaction of NbCl 5 , Al, A 1 X 3 , and mesitylene in DME at -15 °C, which is a rare example of a bis(arene) group 5 complex being accessible via solution methods rather than metal vapor synthesis techniques. 590 ' The bis(toluene) complex (r|-C 6 H 5 Me) 2 Nb, and its analogues originating from metal vapor syntheses, have provided a rich reaction chemistry. Thus, (r|-C 6 H 5 Me) 2 features o f these compounds is a coordinated C 6 R 6 ligand which shows (i) substantial folding along the C-l-C-4 axis (the dihedral angle can be as large as 34°); (ii) an interruption o f aromaticity within the C 6 R 6 ring which can be described as a 1,4-diene-type 7 i localization; and (iii) the close approaches o f C-l and C-4 to the metal which compare to the values o f Ta-C(sp 3 ) single bond lengths, as indicated in (53).…”
Section: Metal Vapor Synthesis Preparationsmentioning
confidence: 99%
“…2). The niobium species, (II), is of interest because only one other Nb 0 complex has been prepared by a conventional procedure, namely bis(mesitylene)niobium(0) (Calderazzo et al, 1991). Also, the titanate, (III), is a rare example of a compound containing titanium in an oxidation state of À1, precedented only by the related bis(arene)titanates(1À) with arene = benzene and toluene (Bandy et al, 1984), and biphenyl and 4,4 0 -di-tertbutylbiphenyl (Blackburn et al, 1992).…”
Section: Introductionmentioning
confidence: 99%